Prevalence and Determinants of Intrauterine Contraceptive Device Uptake among Childbearing Age Women in Nigeria: A Cross-Sectional Study - Abubakar, Rukayya Zubair; Mulud, Zamzaliza Abdul; Musa, Himrah Yunusa; Mohamad, Norfidah (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To investigate the prevalence and determinants of intrauterine contraceptive device (IUCD) uptake among childbearing-age women in Northern Nigeria. METHODOLOGY: A cross-sectional study was employed among 278 childbearing-age women attending a family planning clinic at Wudil General Hospital in Kano State, Nigeria, from June to August 2022. A nonprobability purposive sampling technique was used to recruit participants. The study included women of childbearing age who were within the reproductive years (18 years and above), have conceived at least once, are still reproductive, and wish to delay future pregnancy for at least a year. The study excluded women with primary or secondary infertility who were confirmed pregnant at the study time and had possible cognitive impairment. Data was collected using a self-administered questionnaire. The data were analyzed by using SPSS software version 25.0. RESULTS: The prevalence of IUCD uptake among participants was 23.0%. There were significant differences in IUCD uptake with the number of children and pregnancies, with women having five or more children being five times more likely to use an IUCD. The univariate logistic regression model test showed a significant association between IUCD uptake and the number of pregnancies but not with other factors, including perceived social support. CONCLUSION: The uptake of IUCDs was significant among women who had five or more children. Involving substantial others like husbands, family members, and peers in the issue of IUCDs as a contraceptive method will still help promote the uptake even though perceived social support was found not to be significant.